To what extent is informal property illegal?: Legal practices in the informal production of land. Reply to Professor Arribas - Barboza De las Casas, Gerson (2024)
Possession has become a central concept in the discussion on land tenancy and adequate housing.That is why it demands a shift from the traditional Civilian Law understanding of its legal nature. This paper aims to response to the Theory of the Resizing of Property - TRP, which argues for a constitutional right of possession to incorporate informal property within it.Using a case study methodology, we argue that, on the one hand, the recognition of rights does not lead to an improvement in dwellers living conditions; and, on the other hand, that informal property, far from being outside the Government, is based on legal practices promoted and recognized by it, which consolidate the informal land tenancy generation.